The Popular Image. - Solomon, Alan (London : ICA (Institute of Contemporary Arts) London, 1963)
D'Arcangelo, Allan ; Dine, Jim ; Indiana, Robert ; Johns, Jasper ; Lichtenstein, Roy ; Oldenburg, Claes ; Rauschenberg, Robert ; Ramos, Mel ; Rosenquist, James ; Thibaud, Wayne ; Warhol, Andy ; Wesley, John ; Wesselman, Tom
biografie
The Popular Image, ICA (Institute of Contemporary Arts) London, October 24 - November 23, 1963
Engels
boek